2011
DOI: 10.1002/14651858.cd009513
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve adherence to antiretroviral therapy in children with HIV infection

Abstract: Interventions to improve adherence to antiretroviral therapy in children with HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…Other reviews on interventions to improve adherence to ART have identified similar limitations, including the paucity of research on adherence enhancing interventions in younger populations, 22 the need for behavioral theories that are relevant to Africa, the lack of data on cost-effectiveness, 86 and methodological limitations. 87 More complex interventions are not necessarily better than simple ones.…”
Section: Agreements or Disagreements With Other Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reviews on interventions to improve adherence to ART have identified similar limitations, including the paucity of research on adherence enhancing interventions in younger populations, 22 the need for behavioral theories that are relevant to Africa, the lack of data on cost-effectiveness, 86 and methodological limitations. 87 More complex interventions are not necessarily better than simple ones.…”
Section: Agreements or Disagreements With Other Reviewsmentioning
confidence: 99%
“…87 One also reported finding studies that improved clinical outcomes without improvements in adherence, suggesting an alternate mechanism for health outcomes in children. 22 Two context specific systematic reviews report that reminders may have beneficial effects on adherence in sub-Saharan Africa, though these effects are small. 88,89 A third noted poor methodological quality and few effective interventions in developed countries.…”
Section: Agreements or Disagreements With Other Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…In young children, the correct use of medicines poses specific challenges to parents, caregivers and health care professionals that are usually not encountered in adults (Matsui, 2007;Breitkreutz and Boos, 2007;Polaha et al, 2008;Bain-Brickley et al, 2011;Terry and Sinclair, 2012). For example, the medicine may not be commercially available in the required strength (a 2 mg tablet needs breaking or splitting to administer a 1 mg dose), the medicine may not be available in a dosage form that the child is able to take (babies cannot swallow large tablets), or the medicine may not be available in a dosage form that the child is willing to take (bad taste; adequate taste, but child does not like it; recalcitrance) (Balakrishnan et al, 2007;Balakrishnan et al, 2006;van Riet-Nales et al, 2011;Walsh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…219,226,227,269,[276][277][278][279] The literature review and systematic review of validated adherence scales will allow the selection of adherence scales that will be able to identify non-adherent patients with chronic cardiovascular disease and explore the patient-specific reasons for non-adherence.…”
Section: Discussionmentioning
confidence: 99%